Institutional proxy voting in South Africa: Process, outcomes and impact - S. Viviers; E. vdM. Smit (South African Journal of Business Management, 2015)
This study investigated the nature of institutional shareholder activism in South Africa with a particular focus on proxy voting as a public form of shareholder discontent. A total of 24 510 votes cast by 17 local investment managementcompanies in 2013 were analysed. Interviews were also conducted with selected investment managers to gain more insight into the proxy voting process at their companies. Based on this data, it was concluded that investment managers preferred to engage with investee companies in private and viewed proxy voting as the last link in the shareholder activism chain. As a result, only 6.6 per cent of all votes were `against' resolutions tabled by 347 JSE-listed companies in 2013. Resolutions regarding shareholders' endorsement of companies' remuneration policies; the election and re-election of directors, particularly those serving on audit committees; and the issuance of ordinary shares elicited the most opposition. Companies that were excluded from the JSE's Socially Responsible Investment Index in 2013 attracted significantly more oppositionthan their counterparts who were included in the index when seeking shareholder approval on the election and re-election of directors and the placing of shares under the control of directors. The same applied to companies that had low environmental, social and governance disclosure scores in 2013 as regards the issuance of shares. It is recommended, amongst others, that shareholder activism in South Africa be promoted by enhancing investor education and effecting some regulatory changes.
Keywords: 650